Normal Findings on Brain Fluid-Attenuated Inversion Recovery MR Images at 3T - Neema, M.; Guss, Z.D.; Stankiewicz, J.M.; Arora, A.; Healy, B.C.; Bakshi, R. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Fluid attenuated inversion recovery (FLAIR) MR imaging of the brain has become a routine tool for assessing lesions in patients with suspected neurologic disorders. There is growing interest in 3T brain FLAIR MR imaging but little normative data are available. The purpose of this study was to evaluate the frequency and topography of cerebral hyperintensities seen with FLAIR MR imaging of the brain at 3T in a normal population and compare those findings to 1.5T.MATERIALS AND METHODS: Whole-brain 2D FLAIR MR imaging was performed in 22 healthy controls (mean age, 44 ± 8 years; range, 30–53 years) at 3T. Fifteen of these subjects also underwent 2D FLAIR at 1.5T, with similar optimized parameters and voxel size. Cerebral hyperintense areas, including discrete foci, anterior and posterior periventricular capping, diffuse parenchymal hyperintensity, septal hyperintensity, corticospinal tract hyperintensity, and CSF flow artifacts were assessed. The Spearman rank test assessed the correlation between discrete hyperintense foci and age. The Wilcoxon signed rank test compared foci detectability at 3T versus 1.5T.RESULTS: FLAIR at 3T commonly showed hyperintensities such as discrete foci (mean, 10.68 per subject; at least 1 present in 68% of subjects), anterior and posterior periventricular capping, diffuse posterior white matter hyperintensity, septal hyperintensity, corticospinal tract hyperintensity, and ventricular CSF flow artifacts. FLAIR at 3T showed a higher hyperintense foci volume (170 ± 243 versus 93 ± 152 mm3, P < .01) and number (9.4 ± 13 versus 5.5 ± 9.2, P < .01) than at 1.5T. No significant differences (P = .68) in the length/diameter of individual discrete hyperintense foci were seen between 3T and 1.5T. Discrete foci volume (r = 0.72 at 3T, r = 0.70 at 1.5T) and number (r = 0.74 at 3T; r = 0.69 at 1.5T) correlated with age to a similar degree on both platforms. All discrete foci were confined to the noncallosal supratentorial white matter. The other nonfocal hyperintensities (anterior and posterior periventricular capping, diffuse parenchymal hyperintensity, septal hyperintensity, corticospinal tract hyperintensity, and CSF flow artifacts) were generally more common and prominent at 3T than at 1.5T.CONCLUSIONS: Discrete and diffuse parenchymal brain white matter FLAIR hyperintensities are more common and prominent at 3T than at 1.5T in healthy volunteers.